CONSIDERATIONS ON ENTITY'S RISK ANALYSIS - MIRELA MONEA (Annals of the University of Petrosani: Economics, 2014)
In the present paper, because of the complexity of this topic, the purpose is to discuss the main aspects involved by risk analysis; starting with few conceptual approaches about risk and to outline the contributions about methods to assess different risks categories, especially methods to assess bankruptcy risk prediction (entity insolvency) from economic literature. The methods used to estimate bankruptcy risk are based on the score function which helps to find if an entity is confronted with financial difficulties. The score functions are a diagnosis method elaborated relying on the discriminant analysis, allowing to assess and to predict the bankruptcy risk of the entity using a set of relevant financial ratios.